2007
DOI: 10.1016/j.ijgo.2007.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum urinary retention after cesarean delivery

Abstract: Our results revealed PUR was a common phenomenon in patients who had a cesarean delivery, and morphine-related postoperative analgesia was the main contributing factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 11 publications
1
35
4
2
Order By: Relevance
“…Postpartum urinary retention can cause irreversible damage to the detrusor muscles and parasympathetic nerve fibers within the bladder wall, which might affect detrusor function [8,10,15,16]. Bladder atony, which occurs secondary to the increased levels of progesterone during pregnancy, and early puerperium might contribute to this damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postpartum urinary retention can cause irreversible damage to the detrusor muscles and parasympathetic nerve fibers within the bladder wall, which might affect detrusor function [8,10,15,16]. Bladder atony, which occurs secondary to the increased levels of progesterone during pregnancy, and early puerperium might contribute to this damage.…”
Section: Discussionmentioning
confidence: 99%
“…A PVRBV of more than 150 mL has been used for comparison in published data and research purposes [10]. Ultrasound coupled with duration of labor seems to be a good method for diagnosis of PUR.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Postpartum retention occurs in a range of 0.1–14.1% after vaginal delivery and up to 24.1% after cesarean delivery. [121314] We observed that postoperative and postpartum patients may still be prone to AUR following discharge. The therapeutic approach to such emergencies is straightforward and usually does not necessitate further diagnostic evaluations.…”
Section: Discussionmentioning
confidence: 98%
“…In women who undergo caesarean section, a postvoid residual volume of more than 150 ml has an overall postpartum incidence of between 3 and 24%, and is associated with multiple pregnancy, low body mass index, failure to progress in labour and morphine postoperative analgesia [33,34].…”
Section: Postpartum Voiding Difficultiesmentioning
confidence: 99%